2010 12th IEEE Intersociety Conference on Thermal and Thermomechanical Phenomena in Electronic Systems 2010
DOI: 10.1109/itherm.2010.5501421
|View full text |Cite
|
Sign up to set email alerts
|

From chip to cooling tower data center modeling: Part I Influence of server inlet temperature and temperature rise across cabinet

Abstract: To achieve reductions in the power consumption of the data center cooling infrastructure, the current strategy in data center design is to increase the inlet temperature to the rack, while the current strategy for energy-efficient system thermal design is to allow increased temperature rise across the rack. Either strategy, or a combination of both, intuitively provides enhancements in the coefficient of performance (COP) of the data center in terms of computing energy usage relative to cooling energy consumpt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
32
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(33 citation statements)
references
References 3 publications
0
32
0
1
Order By: Relevance
“…It can be seen that the locations of the cold and hot regions differ according to the fan mode. This raises the possibility that appropriate fan control could avoid having to lower the set point, thereby avoiding unnecessary power consumption [5]. Finally, we regard the heat generated by each server as a disturbance.…”
Section: System Modeling Of Data Center and Fan Control Policymentioning
confidence: 99%
See 1 more Smart Citation
“…It can be seen that the locations of the cold and hot regions differ according to the fan mode. This raises the possibility that appropriate fan control could avoid having to lower the set point, thereby avoiding unnecessary power consumption [5]. Finally, we regard the heat generated by each server as a disturbance.…”
Section: System Modeling Of Data Center and Fan Control Policymentioning
confidence: 99%
“…4 If the reduction scheme is applied to all 723 sensing data instead of only roughly 70 in each loop, each value of λ j − λ j−1 in Step 2 is too small for the division. 5 Except for the selection of the similarity measure or entropy between data, there is little difference between the PSD-based approach in Step 1 and the mutual information-based approach presented by [22].…”
Section: Parameter Identification and Data Reductionmentioning
confidence: 99%
“…In [42], A. Qouneh et al provide a comparative and quantitative analysis of cooling power as varying processor utilization and adjusting the server room temperature accordingly. For further analysis of the power consumption of the cooling facility, some models have been presented in [40,41] which model the power consumption based on thermo-fluid principles. However, based on our analysis of real datacenter setups of our industrial partners in this work, we have observed that an alternative procedure can be used, where PUE mainly depends on the temperature set-point of server room (T room ), outside temperature (T out ), and total power consumed by servers (P cl ).…”
Section: ) Cooling Facilitymentioning
confidence: 99%
“…However, Moore's 46 law [6], which states that transistor density doubles every 2 years, continues to be true 47 nowadays. This means that, due to the exponential increase in IT energy density, in few years 48 the energy density of the IT equipment will reach values up to 50 kW/rack and therefore the 49 solely use of air cooling system will be insufficient to evacuate all the heat generated by the 50 servers [7]. To overcome this problem the data centre industry is already investigating and 51 implementing the use of liquid cooling systems due to the higher heat removal capacity and the 52 ability to cool specific system components to a greater degree [8].…”
mentioning
confidence: 99%
“…Generally the servers and the cooling system are modelled 88 with the heat transfer equation, considering convection and conduction mechanisms. Breen et al 89 [7] performed a thermal equilibrium model of an air cooled rack to obtain flow rate, pressure 90 drop and heat transfer coefficients that were used to characterize the system. Douchet et al [8] According to the water cooling piping configuration, the system can be defined to be in parallel 132 or in series configuration.…”
mentioning
confidence: 99%